2008
DOI: 10.1161/atvbaha.108.174995
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Notch4 Activity Elicits Endothelial Cell Activation and Apoptosis

Abstract: Objective— Notch signaling pathway controls key functions in vascular and endothelial cells (EC). However, little is known about the role of Notch in allografted vessels during the development of transplant arteriosclerosis (TA). This study investigated regulation of the Notch pathway on cardiac allograft arteriosclerosis and further examined its implication in EC dysfunction. Methods and Results— Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 36 publications
5
57
0
1
Order By: Relevance
“…For example, it has been shown that impaired Notch4 activity in graft endothelium of transplant atherosclerosis results in vascular cell adhesion molecule-1 expression and endothelial cell apoptosis. 27 The increased inflammation observed in our mutants might represent the outcome of diminished Notch function both in macrophages and endothelium, with the effect that the endothelial phenotype is dominant.…”
Section: Notch Mutant Valve Tissue Displays Hallmarks Of Cavdmentioning
confidence: 87%
“…For example, it has been shown that impaired Notch4 activity in graft endothelium of transplant atherosclerosis results in vascular cell adhesion molecule-1 expression and endothelial cell apoptosis. 27 The increased inflammation observed in our mutants might represent the outcome of diminished Notch function both in macrophages and endothelium, with the effect that the endothelial phenotype is dominant.…”
Section: Notch Mutant Valve Tissue Displays Hallmarks Of Cavdmentioning
confidence: 87%
“…Notch-4 in arterial endothelial cells enhances the expression of VCAM-1 in the absence or presence of a pro-inflammatory stimulus (51). Furthermore, Notch-1 induces the expression of VCAM-1 by endothelial cells in the absence of inflammatory cytokines and potentiates the IL1␤-dependent VCAM-1 upregulation by interacting with the NF-kB pathway (52).…”
Section: Egfl7 Regulates Endothelial Activation During Inflammationmentioning
confidence: 99%
“…No significant change in Notch1 was observed. Down-regulation of Notch4 was mainly driven by the graft's ECs [88]. In cultured ECs, Notch4 exhibited an anti-inflammatory function by reducing the TNF-mediated induction of vascular cell adhesion molecule-1 (VCAM-1) that plays a crucial role in the recruitment of immune cells to inflammatory sites [88].…”
Section: The Notch Pathwaymentioning
confidence: 99%